2018
DOI: 10.1103/physreva.98.043434
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum distribution in Rydberg states excited by a strong laser pulse

Abstract: We study the excitation to Rydberg states in the interaction of the hydrogen atom with a short strong laser pulse. Utilizing solutions of the time-dependent Schrödinger equation we find that the parity of the populated angular momentum states agrees with the selection rules for multiphoton resonant absorption at low intensities, if the pulse length is not too short. In contrast, the parity effect cannot be observed for ultrashort pulses as well as for long pulses at high intensities. We further identify signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(43 reference statements)
1
3
0
1
Order By: Relevance
“…Figure 3(c) shows the sum of the excitation probability over all odd and even l states. At low intensity, the parity effect is observed for both CEPs with excitation to odd (even) l occurring when an even (odd) number of photons are absorbed, consistent with the expectation from the MP model [32,40].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Figure 3(c) shows the sum of the excitation probability over all odd and even l states. At low intensity, the parity effect is observed for both CEPs with excitation to odd (even) l occurring when an even (odd) number of photons are absorbed, consistent with the expectation from the MP model [32,40].…”
supporting
confidence: 83%
“…The population is spread across a range of quantum states with odd and even l's populated in each n-photon absorption channel. Venzke et al [40] previously showed that the parity effect can break down with few-cycle pulses, where it was proposed to be a consequence of the bandwidth of the pulse. However, here we show that parity is observed in the low-intensity regime but depends on the CEP at higher intensities.…”
mentioning
confidence: 99%
“…The wavefunction is propagated in time using the Crank-Nicolson method with a time step of 0.01 a.u. In test calculations the numerical code was compared against results from a previously used 2D cylindrical code [22], results from time-dependent perturbation theory in the appropriate intensity and frequency regimes, as well as results reported in the literature [23]. Quantitative agreement was achieved.…”
Section: Numerical Solution Of Time-dependent Schrödinger Equationmentioning
confidence: 99%
“…强场RSE过程形成的里德伯态的量子态分布 最近几年也引起了研究者的关注, 这部分工作主要 集中在理论研究上. Eichmann等 [80] 计算得到了 800 nm强激光场中He*的主量子数n分布, 同时, 他们通过计算主量子数为n的里德伯态的激发概 率和存活概率, 指出n > 15的态几乎不受强场的…”
Section: 原子强场Rse的量子态分布unclassified